Peran Kepemimpinan Kepala Desa Dalam Meningkatkan Pembangunan Desa - Tagaku, Andrias (Peneliti.net, 2026)
This research was conducted in Falila Village, South Morotai District, Pulau Morotai Regency, North Maluku Province. In order to improve village development, the role of leadership from the village head is very important. The leadership of the village head has a significant influence in realizing community participation in development activities. Community participation takes various forms, ranging from direct involvement in government programs to indirect contributions, such as financial support, labor, ideas, and opinions in the formulation of village government policies. The purpose of this study is to examine the extent of the village head’s leadership role in improving village development in Falila Village, South Morotai District, Pulau Morotai Regency. The data collection techniques used in this research include observation, interviews, documentation studies, and literature review. The data analysis technique employed is descriptive qualitative analysis, which presents the data obtained from the research object and subsequently draws conclusions based on the findings. The results of the data presentation indicate that the leadership role of the village head in improving village development in Falila Village, South Morotai District, Pulau Morotai Regency, has not been implemented effectively. Therefore, an improvement in the leadership role of the village head is still needed so that community participation can be more clearly reflected in all activities carried out in Falila Village. This can be achieved by applying a democratic leadership style.